2019
DOI: 10.3390/su11184858
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Openness of Firms’ External Search Strategies on Exploratory Innovation and Exploitative Innovation

Abstract: Innovation activities of private firms are crucial for sustainable economic growth in every society. Therefore, the majority of firms around the world spend large amounts of capital (money, time, and human resources) in searching for novel innovative opportunities in the marketplace. In our study, we sought to understand how the openness of firms’ external search strategies (external search breadth and external search depth) affects firms’ innovation capabilities as measured by awareness, decision-making, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…In order to have multiple sources of new knowledge, collaboration with external parties is important (Olander et al, 2014;Patel et al, 2012) and close ties will further facilitate the sharing of confidential information that will benefit the ambidextrous orientation of the firm (Dezi et al, 2019;Xie et al, 2019). Previous studies also confirmed that if a firm continues to pursue external sourcing of new knowledge, then it will be able to identify an opportunity to enter a new market or create a new market, concomitantly generates the quintessential information for the firm to balance up its exploration and exploitation related activities (Sahi et al, 2019;Tang et al, 2019). From the same perspective, an ambidextrous firm can gain a competitive advantage in conjunction with EKS due to its mature development roadmap that continues to search for new ideas that can be incorporated into existing innovation strategy (Vrontis et al, 2017).…”
Section: Knowledge Management and Organizational Ambidexteritymentioning
confidence: 96%
See 1 more Smart Citation
“…In order to have multiple sources of new knowledge, collaboration with external parties is important (Olander et al, 2014;Patel et al, 2012) and close ties will further facilitate the sharing of confidential information that will benefit the ambidextrous orientation of the firm (Dezi et al, 2019;Xie et al, 2019). Previous studies also confirmed that if a firm continues to pursue external sourcing of new knowledge, then it will be able to identify an opportunity to enter a new market or create a new market, concomitantly generates the quintessential information for the firm to balance up its exploration and exploitation related activities (Sahi et al, 2019;Tang et al, 2019). From the same perspective, an ambidextrous firm can gain a competitive advantage in conjunction with EKS due to its mature development roadmap that continues to search for new ideas that can be incorporated into existing innovation strategy (Vrontis et al, 2017).…”
Section: Knowledge Management and Organizational Ambidexteritymentioning
confidence: 96%
“…For this study, the theory of RBV, KBC, DC, and OA will substantiate the postulated hypotheses and the hypothesized conceptual framework. RBV stresses upon firm's resources that are valuable, rare, not able to emulate, and nonsubstitutable (Barney, 1991;Camisón & Villar-López, 2014;Tang et al, 2019) as the main component of the firm to gain competitive advantage. However, such resources are not perpetually available as the market dynamic will render once a valuable resource is considered valueless for the firm (Barney, 1991).…”
Section: Underlying Theorymentioning
confidence: 99%
“…Innovative market changes offer new growth opportunities [32,39] supported by the combination of product newness, original market-product strategies, and business policies focused on satisfying market niches. These elements provide additional revenue and growth opportunities to the firm [20,[40][41][42], especially in regions and nations endowed with a high-approval entrepreneurial environment [43].…”
Section: Innovative Behavior Product Newness and Entrepreneurial Grmentioning
confidence: 99%
“…Such as personality, emotional intelligence, psychological capital, psychological safety, individuals' knowledge and skills [14][15][16][17]. On the other hand, related research suggests that employee creativity is generated by external factors, such as family motivation, management characteristics, constructive leadership, team goal orientation, high-performance work system and organizational climate [18][19][20][21][22][23][24][25][26][27]. In recent years, scholars have begun to pay attention to the impact of new features of the digital era such as social media, information conflict and cooperation models on employee creativity [28][29][30].…”
Section: Introductionmentioning
confidence: 99%